LISTEN WHILE YOU WORK? The Attitude of Healthcare Professionals to Music in the OR - Faraj, Adnan; Wright, P; Haneef, J H S; Jones, Adrian (Operating Room Nurses Association of Canada Journal, 2015)
Although the playing of music is commonplace in the operating theatre, there is nothing in the literature examining whether staff feel this is beneficial. Questionnaires were distributed amongst a random selection of staff in practice at a district general hospital: medical staff from a range of surgical specialities, anaesthetists, and all grades of perioperative staff (nurse/operating department practitioners/healthcare assistants) were encouraged to participate. There were 121 health professionals in total working in the operating theatres. The authors compared the responses to each question amongst the respondents, to check for the tendency to correlate. Out of the 52 health professionals who responded, 36 stated that music is played in their theatre either every day, or two to three times a week. Only five respondents felt that this was too often. Fifteen percent of medical staff were of the opinion that the nursing staff controlled the choice of music. Nursing staff were almost evenly split in thinking that nursing staff, surgical staff and the whole theatre team controlled the choice of music. The majority of both nursing and medical staff felt that they enjoyed their work more and performed better when music was played in theatre. The study concluded that the majority of theatre staff found listening to music while they work a positive experience. The potential for music to have a distracting or detrimental effect on a minority of individuals should always be considered.